2012
DOI: 10.9798/kosham.2012.12.4.085
|View full text |Cite
|
Sign up to set email alerts
|

Slope Stability Characteristic of Unsaturated Weathered Granite Soil in Inje considering Antecedent Rainfall

Abstract: Unsaturated geotechnical properties and other factors(rainfall characteristic, geomorphology, etc) have to be considered in order to evaluate the stability of real slope. Even though antecedent rainfall is also an important factor on the slope stability, it is rarely considered in analysis of slope stability. In this paper slope stability analysis for unsaturated weathered granite soil in Inje was conducted considering antecedent rainfall. Effect of antecedent rainfall was considered in analysis by using initi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Generally, rainfall-initiated landslides are strongly governed by rainfall characteristics at the time of the rainfall event, but they can also be affected by antecedent rainfall (i.e., rainfall preceding a rainfall event). Antecedent rainfall is an important factor to determine the initial soil matric suction conditions by inducing gradual increases in soil moisture and groundwater level, which can influence the initiation of landslides (Lee et al 2012). Based on realtime monitoring of four slopes in Singapore, Rahardjo et al (2008) demonstrated that the role of antecedent rainfall in the development of the worst pore-water pressure condition was more significant in residual soils with low permeability than in those with high permeability.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, rainfall-initiated landslides are strongly governed by rainfall characteristics at the time of the rainfall event, but they can also be affected by antecedent rainfall (i.e., rainfall preceding a rainfall event). Antecedent rainfall is an important factor to determine the initial soil matric suction conditions by inducing gradual increases in soil moisture and groundwater level, which can influence the initiation of landslides (Lee et al 2012). Based on realtime monitoring of four slopes in Singapore, Rahardjo et al (2008) demonstrated that the role of antecedent rainfall in the development of the worst pore-water pressure condition was more significant in residual soils with low permeability than in those with high permeability.…”
Section: Introductionmentioning
confidence: 99%